Glycaemic control of Type 2 diabetes in older patients visiting general practitioners: An examination of electronic medical records to identify risk factors for poor control. (July 2019) - Xia, Ting; Turner, Lyle; Enticott, Joanne; Mazza, Danielle; Schattner, Peter
Abstract: Objective: To investigate factors associated with glycaemic control of diabetes in older patients in the general practice setting in metropolitan Melbourne, Australia. Method: This retrospective study used the data from 10, 257 patients aged ≥ 65 years with Type 2 diabetes from the Melbourne East Monash General Practice Database (MAGNET), 2009–2014. Poor glycaemic control was defined as HbA1c ≥ 9.0%. Univariate and multivariate analyses were conducted to assess the association between risk factors and glycaemic control. Results: Of the total 10, 257 patients, 6819 (66.5%) had their HbA1c recorded within a period of 2 years prior to their last GP visit. Between 4% and 6% had HbA1c level ≥ 9.0%. Robust predictors of poor glycaemic control were found to be decreasing age group (OR = 0.77, 95% CI: 0.65–0.90) and prescribed insulin (OR = 2.83, 95% CI: 2.41–3.32). Conclusion: One third of older patients with Type 2 diabetes did not have HbA1c recorded in the previous 2 years, despite clinical guidelines recommending at least annual testing. Many older patients had good glycaemic control, however the findings indicate that those aged 65–74 and those prescribed insulin may require special care and management to achieve this.